Squids will be squids : fresh morals, beastly fables - Scieszka, Jon.; Smith, Lane.; Leach, Molly (New York : Viking, 1998)
Contemporary fables with tongue-in-cheek morals address such topics as homework, curfews, and television commercials.
6.0
K-3
K-3
Wilson's Children
School Library Journal
Pub Weekly
Keywords: Humorous stories; Fables; Humorous fiction; Fables